Using stone dust as an improvement material for cement gravel column - Raksiri Sukkarak; Pornkasem Jongpradist; Panich Voottipruex; Pitthaya Jamsawang; Suraparb Keawsawasvong; Teerawut Pansuwannakun; Ittipon Meepon (Case Studies in Construction Materials)
Stone dust is a voluminous solid waste material, a by-product of stone aggregate processing, generally dumped in landfills. Recently, stone dust was utilized as fine aggregates in various concrete applications with a suitable replacement, which can significantly mitigate environmental pollution. This study investigates the potential of utilizing stone dust as a sustainable enhancement material for cement gravel columns in geotechnical engineering applications. A cement gravel (CG) column was employed for ground improvement in foundation engineering, offering increased load-bearing capacity and structure stability. This research explores the feasibility of incorporating stone dust into cement gravel columns to enhance their mechanical properties and sustainability profile. Fifteen mixture designs were prepared to investigate the effect of stone dust (0, 5, 10, 15, and 20 % by weight of highest porous sample) on the engineering and physical properties of cemented gravel samples at 7 and 28 days. The compressive strength of CG material increases with the addition of stone dust until it attains its optimum content of 10 % of stone dust. The results confirm that CG meets porous concrete’s hydraulic conductivity and mechanical performance requirements. The unconfined compressive strength (UCS) test showed that 10 %-20 % cement-content CG samples exhibited compressive strengths between 12 and 83 ksc, meeting low-to-medium load-bearing construction requirements. The stone dust affects the failure mechanisms of the CG sample, which is discussed. SEM, EDX and XRD analyses further established the existence of the stone dust within the CG particles. Additionally, stone dust offers sustainability benefits by reducing waste generation and contributing to circular economy principles